2011
DOI: 10.3390/ijerph8051287
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis of Nutritional Content of Prickly Pads (Opuntia ficus indica) at Varied Ages in an Organic Harvest

Abstract: Opuntia ficus indica, also known as prickly pads, are an important part of the human diet and are also used as forage for livestock. This is an interesting vegetable due the environmental conditions in which it grows and its resistance to climatic extremes; however, little is known about its nutritional properties, especially in the later stages of maturity. The objective of this study was to determine the composition of organic prickly pads (Opuntia ficus indica) at differing stages of growth maturity. Chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 17 publications
4
52
3
Order By: Relevance
“…The mineral composition of Opuntia fruits found is influenced by the specific environmental conditions and the geology of the production areas, 38 in accordance with studies conducted in samples of other botanical origin from various European areas. 39 In fact, the combination of environmental factors such as sun exposure and pedoclimatic characteristics contributes to make cultivated products unique in quality and healthiness.…”
Section: Mineral Contentssupporting
confidence: 87%
“…The mineral composition of Opuntia fruits found is influenced by the specific environmental conditions and the geology of the production areas, 38 in accordance with studies conducted in samples of other botanical origin from various European areas. 39 In fact, the combination of environmental factors such as sun exposure and pedoclimatic characteristics contributes to make cultivated products unique in quality and healthiness.…”
Section: Mineral Contentssupporting
confidence: 87%
“…The betacyanins identified in Opuntia fruits include betanidin, betanin, isobetanin, isobetanidin, neobetanin, phyllocactin, and gomphrenin I [3, 4, 2426]. O. streptacantha (Cardona cultivar), (Rojalisa cultivar), and O. megacantha (Naranjona cultivar) contain traces of betanidin 5-O- β -sophoroside [34].…”
Section: Cladodes Chemical Compositionmentioning
confidence: 99%
“…As it is well known, nopal has antinutrimental compounds such as calcium oxalates, but Contreras-Padilla et al (14) found that its concentration decreases with maturity, as more mature nopals contain less calcium oxalate (11.4 mg, 40 days, and 4.25 mg/g, 135 days) (1215). When nopal is dehydrated, its nutrient contents per net weight increase, as does its shelf life.…”
mentioning
confidence: 99%